Peculiarities of Preoperative Planning of Total Hip Arthroplasty in Patients with Hip-Lumbar Syndrome - Sulyma, O.M.; Kalashnikov, O.V.; Galuzynskyi, O.A.; Pidgaietskyi, V.M.; Osadchuk, T.I.; Zaiets, V.B.; Moroz, M.D. (TERRA ORTHOPAEDICA, 2021)
Summary. At present, no scheme of approach to surgical treatment of patients with hip-lumbar syndrome (HLS) depending on the type of vertical posture and the type of bone formation and progression of coxarthrosis is developed. The decision of these questions, interesting from the scientific and practical point of view, is an actual task of modern orthopedics and defines features of preoperative planning of total hip arthroplasty (THA) in patients with HLS.Objective: to determine the features of preoperative planning of total hip arthroplasty in patients with hip-lumbar syndrome.Materials and Methods. The basis for the development of recommendations for preoperative planning of THA in patients with HLS was the data of retrospective analysis of medical histories of 138 patients who underwent hip arthroplasty in the Department of Orthopedics and Traumatology of Adults of SI “Institute of Traumatology and Orthopedics of NAMS of Ukraine”. The data of the clinical study of 506 patients with idiopathic, dysplastic and post-traumatic coxarthrosis conducted earlier were also taken into account, and the tactics of treatment in cementless hip arthroplasty was developed.Results. It was determined that the vertical posture affects the progression of coxarthrosis and the nature of the lesion of the lumbar spine in patients with HLS. Patients with a certain hypolordotic posture and a rapid course of coxarthrosis are recommended to undergo primary decompression of the spinal roots and THA at the second stage. In other cases, the initial implementation of THA is recommended. Recommendations for the use of the type and method of fixation and coverage of the leg of the endoprosthesis depending on the type of bone formation in the HLS of the examined patients are developed.Conclusions. Taking into account the features of preoperative planning of THA in patients with HLS will reduce the number of negative results and complications of this category of orthopedic patients.